The Effect Of Visual Warning On Cigarette Packs of Intention to Quit Smoking At Online Taxibike Rider In Banda Aceh - Izzati, Rahmi; Usman, Said; Saputra, Irwan; Marthoenis, Marthoenis; Martunis, Martunis (STRADA : Jurnal Ilmiah Kesehatan, 2020)
According to WHO, Indonesia was the third largest country with the biggest number of smokers in the world after China and India. Riskesdas 2018 stated the number of smokers in Indonesia was very high, that was 33 percent with male smoker by 63 percent. Government set smoking hazards warning and included health warnings and informations on cigarette packs, however these did not show a significant effect.This research used analytics survey with cross sectional approach on online taxibike riders by sampling using purposive sampling method so that 155 samples were obtained. There were a significant effect on the intention to quit smoking with variable image illustration OR=3.01 P=0.008, typography OR=3.62 P=0.003, color OR=3.37 P=0.04, layout OR=3.48 P=0.002 and the most influence variable, visual warnings in color forms OR=2.29 P=0.010. The result presented that visual warning signs on cigarette packs could rise the intention to quit smoking on online taxibike riders.